2019
DOI: 10.1016/j.jde.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Critical exponent for nonlinear damped wave equations with non-negative potential in 3D

Abstract: We are studying possible interaction of damping coefficients in the subprincipal part of the linear 3D wave equation and their impact on the critical exponent of the corresponding nonlinear Cauchy problem with small initial data. The main new phenomena is that certain relation between these coefficients may cause very strong jump of the critical Strauss exponent in 3D to the critical 5D Strauss exponent for the wave equation without damping coefficients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…, and θ = 2, we have p 1 = p 2 = 1, p 3 = 4/3, and thus recover the blow-up result in [4] for 1 < p < p S (5).…”
Section: (Iii) Critical Damping and Potentialsupporting
confidence: 80%
See 1 more Smart Citation
“…, and θ = 2, we have p 1 = p 2 = 1, p 3 = 4/3, and thus recover the blow-up result in [4] for 1 < p < p S (5).…”
Section: (Iii) Critical Damping and Potentialsupporting
confidence: 80%
“…In [4], Georgiev, Kubo and Wakasa showed that the critical power for the radial solutions is the shifted Strauss exponent p = p S (3 + 2), for a special case in R 3 , with damping and potential coefficients satisfying the relation…”
Section: Introductionmentioning
confidence: 99%
“…We remark that as for regular damping and potential terms, it has been shown in [3] that p c (3, 2, 2) = p c (5, 0, 0) and the upper and lower bounds for T ε,2,2 (3, p) coincides with those of T ε,0,0 (5, p). Now, we are in a position to state our main result in this paper about the upper bound of lifespan of solutions to (1.1), under the following technical requirements.…”
Section: Introductionmentioning
confidence: 59%
“…The former one is easy to verify by a direct calculation, so we leave it to readers. As for the latter one, we use the idea comes from [3]. To begin with, we introduce a proposition.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation